Comparing laboratory and online settings: equivalence in training and transfer effects for training task-order coordination processes - Darnstaedt, Daniel A.; Langsdorf, Leif; Schubert, Torsten (Frontiers in Psychology, 2024)
Introduction The literature on dual-task training suggests reductions in task-coordination costs with extensive practice, yet such regimens are resource-intensive. This study investigates the feasibility of online assessments for cognitive training studies by comparing training and transfer effects on task-order coordination (TOC) skills in laboratory versus online settings. Methods We conducted a 5-day training regimen including pre-and post-test. Sixty-two participants completed training either in our laboratory or online via Pavlovia. They were assigned to one of two training order conditions, either practicing two visual-manual tasks in a dual-task situation with fixed task order or with random task order. Performance metrics included reaction time (RT) and error rates for trained and untrained tasks to assess TOC costs before and after the training. Data from both setting conditions (laboratory vs. online) were compared. Results Firstly, data of both settings revealed training-order specific training and transfer effects for TOC costs on RT level. Random task order training improved TOC for trained and untrained tasks, whereas fixed order training did not. Secondly, cross-setting analyses, both frequentists and Bayesian, confirmed these effects and revealed no reliable impact of setting on outcomes. Discussion This research carries two significant implications. Our findings demonstrate the acquisition of task-order coordination skills, extending prior research on improving task-coordination in dual-task situations. Additionally, the robust effects for such improvements were independent of specific tasks and setting (whether investigated online or in the laboratory), supporting the use of online testing in cognitive training regimens for resource savings without compromising quality.